Education 4.0: Using Web-based Massachusetts Institute of Technology (MIT) App Inventor 2 in Android Application Development - Sabado, Wilber B. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – The use of an online platform called the (MIT) Massachusetts Institute of Technology App Inventor 2 provided an easy-to-use tool for students in developing an Android mobile application. Education 4.0 is about the use of technology like the MIT App Inventor 2. The MIT App Inventor 2 is an alternative to developing mobile Android applications. Method – This paper utilized a Descriptive Research Design which used a quantitative method. The survey questionnaires were validated by IT experts. Results – 90% of the respondents are Very Satisfied in learning the MIT App Inventor 2 platform. 93 respondents answered and marked the use of MIT Inventor 2 as Very Satisfied and 7 respondents marked the use of MIT Inventor 2 as Satisfied. Conclusion – The students were able to develop Personal Mobile Apps, Educational Mobile Apps, and Internet of Things Mobile Apps using the MIT App Inventor 2. The students were able to integrate Arduino microcontrollers into their Android apps. Recommendations – To integrate the use of MIT App Inventor 2 in K12 courses. Research Implications – This research seeks to promote the use of MIT App Inventor 2 to help non-programmers in developing an Android-based mobile application. Practical Implications – This research proves that technology integration enhances work efficiency. Social Implications – This research shows opportunities for students to use technology.